Effects of high-isoflavone soy diet vs. casein protein diet and obesity on DMBA-induced mammary tumor development - HAKKAK, REZA (D.A. Spandidos, 2011)
Obesity and elevated serum insulin growth factor-1 (IGF-1) level are major risk factors in the development of breast cancer. We investigated the long-term effects of high-isoflavone soy intake and obesity on 7,12-dimethylbenz(a)anthracene (DMBA)-induced mammary tumor development and on serum IGF-1 and binding protein (IGFBP-3) levels. Lean and obese female Zucker rats fed casein or high-isoflavone soy protein were orally gavaged at age 50 days with DMBA and sacrificed after 147 days. The majority of lean casein-fed rats (69%) developed mammary tumors compared to 50% in lean soy-fed rats (P=0.176). In the obese groups, 76% of soy-fed rats developed mammary tumors compared to 15% of obese casein-fed rats (P<0.001). At age 43 days, IGFBP-3 was increased in the lean soy-fed rats compared to the lean casein-fed rats (P<0.05). At age 99 days, soy- and obese casein-fed rats exhibited increased serum IGF-1 compared to the lean rats and this increase was maintained for the rest of the experiment (P<0.05). Obese rats fed casein exhibited increased IGFBP-3 levels (P<0.001). However, obese rats fed soy exhibited a significant decrease in IGFBP-3 levels compared to the lean soy-fed rats (P<0.001) and a significant decrease in IGFBP-3 levels compared to the obese casein-fed rats (P<0.001). At age 197 days, IGFBP-3 levels were increased in obese casein-and soy-fed rats (P<0.001). The results suggest that female Zucker rats fed casein diets are protected against DMBA-induced mammary tumors, which is not the case for those on high-isoflavone soy diet, and changes in the concentration of serum IGFBP-3 may contribute to the incidence of DMBA-induced mammary tumors.